The use of information technology by private college teachers to support the educational process (Journal of the College of Basic Education, 2022)
The research aims to identify the level of information technology currently used in supporting the educational process and to find out the reality of its use in supporting the educational process, as well as to identify the obstacles that prevent the use of information technology in the teaching process, in order to indicate the approved programs to qualify faculty members to use and produce educational programs that The curricula are supported by surveying the opinions of faculty members in a sample of some private colleges in the city of Baghdad - Republic of Iraq (Al-Turath University College, Al-Mansour University College, Al-Rafidain University College, Al-Mamoun College).